The Role of Fucoxanthin in Non-Alcoholic Fatty Liver Disease - Winarto, Jessica; Song, Dae-Geun; Pan, Cheol-Ho (Multidisciplinary Digital Publishing Institute (MDPI), 2023)
Chronic liver disease (CLD) has emerged as a leading cause of human deaths. It caused 1.32 million deaths in 2017, which affected men more than women by a two-to-one ratio. There are various causes of CLD, including obesity, excessive alcohol consumption, and viral infection. Among them, non-alcoholic fatty liver disease (NAFLD), one of obesity-induced liver diseases, is the major cause, representing the cause of more than 50% of cases. Fucoxanthin, a carotenoid mainly found in brown seaweed, exhibits various biological activities against NAFLD. Its role in NAFLD appears in several mechanisms, such as inducing thermogenesis in mitochondrial homeostasis, altering lipid metabolism, and promoting anti-inflammatory and anti-oxidant activities. The corresponding altered signaling pathways are the beta 3-adorenarine receptor (beta 3Ad), proliferator-activated receptor gamma coactivator (PGC-1), adenosine monophosphate-activated protein kinase (AMPK), peroxisome proliferator-activated receptor (PPAR), sterol regulatory element binding protein (SREBP), nuclear factor kappa B (NF-kappa B), mitogen-activated protein kinase (MAPK), protein kinase B (AKT), SMAD2/3, and P13K/Akt pathways. Fucoxanthin also exhibits anti-fibrogenic activity that prevents non-alcoholic steatohepatitis (NASH) development.